Almost perfect sequence modulated multiplexing ion mobility spectrometry. (29th June 2022) - Meng, Qingyan; Jia, Xu; Zhang, Hanghang; Wang, Zhiyan; Liu, Wenjie
Abstract : Rationale: Multiplexing ion mobility spectrometry with multiple ion injection pulses was used to achieve a high duty cycle and thus improve the signal‐to‐noise (S/N) ratio while maintaining high resolving power compared with the traditional single‐pulse signal averaging method. Historically, an ion mobility spectrum was reconstructed by various multiplexing methods including Fourier transform ion mobility spectrometry (FT‐IMS), Hadamard transform ion mobility spectrometry (HT‐IMS), and linear frequency modulation correlation ion mobility spectrometry (LFM‐CIMS) sequence or Barker code. Methods: To achieve an artifact‐free multiplexing ion mobility spectrum, an almost perfect sequence (APS) with correlation technique was proposed to modulate the Bradbury‐Nielson ion gate and was compared with FT‐IMS, HT‐IMS, LFM‐IMS, and the traditional single‐pulse signal averaging method. Results: Experimental results showed that there are no artifact peaks in the APS‐IMS spectra except an inverted mirror peak, and the S/N ratio was improved 5–8 times with a repetition time of 40–60 ms, corresponding to the improvement in the duty cycle. With the same duty cycle and similar acquisition time, APS‐IMS showed a higher S/N ratio than HT‐IMS for its unique autocorrelation response. Conclusions: The APS‐IMS technique offered a higher duty cycle and relatively shorter modulation period compared with reported multiplexing methods and is suitable to track rapidly changing signals without losing information and adding extra transformation artifact peaks.